2023
DOI: 10.3389/fgene.2022.1081478
|View full text |Cite
|
Sign up to set email alerts
|

A four-lncRNA risk signature for prognostic prediction of osteosarcoma

Abstract: Aim: Osteosarcoma is the most common primary malignant tumor of bone. However, our understanding of the prognostic indicators and the genetic mechanisms of the disease progression are still incomplete. The aim of this study was to identify a long noncoding RNA (lncRNA) risk signature for osteosarcoma survival prediction.Methods: RNA sequencing data and relevant clinical information of osteosarcoma patients were downloaded from the database of Therapeutically Applicable Research to Generate Effective Treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…The proteins of nectin-3 interact with TIGIT and iit has been reported that patients with high TIGIT levels exhibited positive correlations with progression-free interval and overall survival [28]. The LncRNA of PVRL3-AS1 expression is decreased in osteosarcoma tissues and osteosarcoma cells, which may be used to predict the survival of osteosarcoma patients [29].…”
Section: Nectin-3 and Cancersmentioning
confidence: 99%
“…The proteins of nectin-3 interact with TIGIT and iit has been reported that patients with high TIGIT levels exhibited positive correlations with progression-free interval and overall survival [28]. The LncRNA of PVRL3-AS1 expression is decreased in osteosarcoma tissues and osteosarcoma cells, which may be used to predict the survival of osteosarcoma patients [29].…”
Section: Nectin-3 and Cancersmentioning
confidence: 99%